2021
DOI: 10.2478/acph-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of COVID-19 protease and HIV inhibitors interactions

Abstract: The epidemic of the novel coronavirus disease (COVID-19) that started in 2019 has evoked an urgent demand for finding new potential therapeutic agents. In this study, we performed a molecular docking of anti-HIV drugs to refine HIV protease inhibitors and nucleotide analogues to target COVID-19. The evaluation was based on docking scores calculated by AutoDock Vina and top binding poses were analyzed. Our results suggested that lopinavir, darunavir, atazanavir, remdesivir, and tipranavir have the best binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…On the other hand, Tran et al reported favorable affinity (between −5.8 and −8.8 kcal/mol) of NRTIs with SARS-CoV-2 3CLpro [64] , one of the most attractive viral targets for an antiviral drug against this virus [65] . Therefore, we also evaluated the binding affinity of 3TC and FTC with the proteolytic site of 3CLpro, obtaining favorable binding energies, although low, for both compounds ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Tran et al reported favorable affinity (between −5.8 and −8.8 kcal/mol) of NRTIs with SARS-CoV-2 3CLpro [64] , one of the most attractive viral targets for an antiviral drug against this virus [65] . Therefore, we also evaluated the binding affinity of 3TC and FTC with the proteolytic site of 3CLpro, obtaining favorable binding energies, although low, for both compounds ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This process involves the prediction of ligand conformation and orientation within a specific binding site, involving algorithms and scoring functions that allow predicting biological activity by evaluating interactions between compounds and potential targets [91]. Both Autodock4 and its graphical interface, AutoDockTools, are available as free and open source software for Microsoft Windows, Mac OS, and Linux systems, Although there is ample evidence of the use of Autodock4 in the search for and development of potential drugs against Cancer, HIV, and COVID-19, among other diseases [92][93][94][95][96][97], its use has also been reported in the training of students in areas related to medicine, bioinformatics, and education [10,[98][99][100].…”
Section: Computational Chemistry Elementsmentioning
confidence: 99%
“…Nevertheless, the recent reports on the promising use of lopinavir/ritonavir, approved anti-HIV drugs, to inhibit SARS-CoV2 [137,138] might be indicating that the repurpose strategy of HIV proteases for SARS-CoV-2 protease was apparently possible. Thran et al [139] reported that lopinavir, darunavir, atazanavir, remdesivir, and tipranavir demonstrated the promising inhibitory properties against 3CLpro-CoV2 with the binding energy ranging from −8.4 to −9.2 kcal/mol. These compounds are the FDA-approved drugs of HIV.…”
Section: Possibility Of Inhibitors Targeting Hiv Protease For Sars-cov2 Proteasesmentioning
confidence: 99%